A Proposed Motivation Programme for Underachieving Students at the Faculty of Engineering, University of Malaya - Siraj, S.F.; Ali, N.M.; Mahadi, W.N.L.; Soin, N.; Dawal, S.Z. (2007)
This paper proposes a motivation programme in arresting the problems of low achievement of some students in the engineering faculty, University of Malaya, Malaysia. Even though the majority of students come up with above average performance, the occurrence of students failing to perform well has caused a lot of concern among the teaching staff. Some major factors have been investigated and through years of monitoring samples of students who came up and seek advice from the authors, it was found that through this programme, the student’s academic performances improved tremendously. It is then agreed that the motivation programme may just be the best solution in upgrading the student’s academic abilities. This paper attempts at drawing out a proper motivation programme which will be effective in addressing the problems of underachieving students.